Day-Of-The-Week Effects: Evidence From The Chinese Stock Markets - Chia, Ricky Chee-Jiun; Liew, Venus Khim-Sen; Syed Azizi Wafa, Syed Khalid Wafa (Serials Publications, 2011)
This study examines the day-of-the-week effects in the Hong Kong, Shanghai and Taiwan stock markets. The current findings on the mean returns and their volatility in the stock markets could be useful in designing the trading strategies and drawing investment decisions. Investors can use the day-of-the-week effects information to avoid and reduce the risk when investing in these 3 stock markets. Further analysis using TGARCH model, uncover asymmetrical market reactions on the positive and negative news, rendering doubts on the appropriateness of the previous research that employed the symmetrical GARCH model in their analysis of day-of-the-week effects.